(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today, concept of sustainability has been considered due to sustainable development implementation, growing population and rapid growth of construction. The sustainability concept is very broad in architecture. Biocompatible architecture subject (green architecture) is one of the most important and challenging issues in sustainability field of todays and future world. Biocompatible (green) architecture is a branch of architecture in which all or parts of a building are covered with green vegetation (plant growth medium) based on environmental and sustainable principles. This architecture style is one of the most innovative approaches in architecture and urbanism, all of which derive from sustainability concept. Although attention to nature and biocompatibility has long been visible in many civilizations and cultures, but this issue is becoming more and more important today due to increased population and construction, high energy consumption in buildings and cities, reduced natural green per capita, air pollution, climate changes and eventually disrupted ecosystem. Beauty of green spaces in urban sector and consequent positive psychological impacts on citizens, which is less discussed, is another important issue of this architecture style. Given the speed and expansion of construction in cities and decline of green spaces, beauty of green spaces will be one of the major challenges for architects and urban planners in future. In this paper, we study and analyze biocompatible architecture (green architecture) in order to expand green buildings and positive psychological effects on citizens.